ANALISIS MANFAAT-BIAYA INSTALASI PENGOLAHAN AIR LIMBAH PT SARI HUSADA YOGYAKARTA - saptutyningsih, endah (Jurnal Ekonomi & Studi Pembangunan, 2002)
There is high rate of growth in Indonesia manufacture industry today. The important role of manufacture industry followed by emerging both positive and negative impact. Negative impact can be seen especially in pollution problems. The objective of this study is to evaluate systematically on benefit and cost in relation to usage at Instalasi Popolasi Air Timbal (IMBAL). To evaluate it the author use sensitivity analysis.